Modelling the criticality of silicon nitride surface imperfections under rolling and sliding contact. (August 2020) - Zolotarevskiy, V.; Kadin, Y.; Vieillard, C.; Hadfield, M.
Abstract: Ceramic rolling elements of hybrid bearings may initially include surface imperfections. In order to provide reliable operation of a bearing, the criticality of such imperfections under rolling contact fatigue is examined by defining them as Star features: intersecting semi-elliptical surface cracks. Parametric study is conducted using Finite Element Method and discussed with help of previously published experimental observations. The effects of the Star feature morphology and configuration, contact pressure and crack face friction are investigated in terms of stress intensity factors. Possible crack propagation scenarios are explained in the present study. Highlights: Artificial imperfection in ceramics mimicking surface defect is modelled by FEM. Risk of crack propagation is assessed in rolling and sliding point contact. Conditions similar to rolling contact fatigue tests are examined numerically. Mechanisms of crack propagation are explained by Fracture Mechanics and experiments.